Home environment and social media as correlates of academic underachievement of high ability secondary school students in Oyo metropolis (2017)
This study examined the relationship between home environment, social media and academic underachievement of high ability secondary school students in Oyo metropolis. The population of this study comprised all high ability Secondary School Students One (SS 1) in Oyo Metropolis. Three hundred respondents were drawn from the twenty schools selected from the four local governments in Oyo Metropolis. Slosson Intelligence Test and Contributions of Home Environment and Social Media Scale were used as instruments. Slosson Intelligence Test was constructed and validated by Slosson (1961) while Contributions of Home Environment and Social Media Scale was designed by the researcher which was later validated and the reliability co-efficient yielded r -0.78. The result of the first hypothesis revealed that there is a significant relationship between home environment and academic underachievement of high ability students. The indication is that the relationship between home environment and academic underachievement of high ability students resulted in the lower r=.68 against p-value .195. The result of the second hypothesis revealed that there is a significant relationship between social media and academic underachievement of high ability students. This indicated that r-crit of .62 against p-value .195. It was recommended that parents should serve as good role models to their high ability children by embarking on good social habits that is worthy of emulation. Parents and teachers must also counsel the high ability students from time to time to be mindful of what they browse on the internet.